Development of sulfur-polyacrylonitrile/graphene composite cathode for lithium batteries - Li, Jing (University of Waterloo, 2013)
Rechargeable lithium sulfur (Li-S) batteries are potentially safe, environmentally friendly and economical alternative energy storage systems that can potentially be combined with renewable sources including wind solar and wave energy. Sulfur has a high theoretical specific capacity of ~1680 mAh/g, attainable through the reversible redox reaction denoted as S8+16Li ↔8Li¬2S, which yields an average cell voltage of ~2.2 V. However, two detrimental factors prevent the achievement of the full potential of the Li-S batteries. First, the poor electrical/ionic conductivity of elemental sulfur and Li2S severely hampers the utilization of active material. Second, dissolution of intermediate long-chain polysulfides (Li2Sn, 2<n<7) into the electrolyte and their shuttle between cathode and anode lead to fast capacity degradation and low Coulombic efficiency. As a result of this shuttle process, insoluble and insulating Li2S/Li2S2 precipitate on the surface of electrodes causing loss of active material and rendering the electrode surface electrochemically inactive. Extensive research efforts have been devoted to overcome the aforementioned problems, such as combination of sulfur with conductive polymers, and encapsulation or coating of elemental sulfur in different nanostructured carbonaceous materials. Noteworthy, sulfur-polyacrylonitrile (SPAN) composites, wherein sulfur is chemically bond to the polymer backbone and PAN acts as a conducting matrix, have shown some success in suppressing the shuttle effect. However, due to the limited electrical conductivity of polyacrylonitrile, the capacity retention and rate performance of the SPAN systems are still very modest, which shows only 67 % retention of the initial capacity after 50 cycles for the binary system. Recently, graphene has been intensively investigated for enhancing the rate and cycling performance of lithium sulfur batteries. Graphene, which has a two-dimensional, one-atom-thick nanosheet structure, offers extraordinary electronic, thermal and mechanical properties. Herein, a sulfur-polyacrylonitrile/reduced graphene oxide (SPAN/RGO) composite with unique electrochemical properties was prepared. PAN is deposited on the surface of RGO sheets followed by ball milling with sulfur and heat treatment. Infrared spectroscopy and microscopy studies indicate that the composite consists of RGO decorated with SPAN particles of 100 nm average size. The PAN/RGO composite shows good overall electrochemical performance when used in Li/S batteries. It exhibits ~85% retention of the initial reversible capacity of 1467 mAh/g over 100 cycles at a constant current rate of 0.1 C and retains 1100 mAh/g after 200 cycles. In addition, the composite displays excellent Coulombic efficiency and rate capability, delivering up to 828 mAh/g reversible capacity at 2 C. The improved performance stems from composition and structure of the composite, wherein RGO renders a robust electron transport framework and PAN acts as sulfur/polysulfide absorber.
Keywords: Li-S batteries; Polyacrylonitrile; Lithium-ion batteries; Energy storage; Chemical Engineering